Straits Settlements Blue Book (imports/exports) 1910 vol.54 (Great Britain : Public Record Office, 1971)
Mengandungi'Straits Settlements return of imports and exports during the year 1910';'Statement of the quantities and value of imports into the colony of the Straits Settlements from other countries and exports there to in 1909 and 1910'.